ASSESSMENT SYSTEM IN CURRICULUM 2013 OF ELEMENTARY SCHOOL IN SUMENEP DISTRICT MADURA ISLAND - Dian Eka Indriani (STKIP Singkawang, 2016)
New curriculum has been implemented by Indonesia government in an effort to improve quality of education in 2013. Curriculum 2013 is implemented only in grade I, IV, VII and Class X against 6,325 target schools. In 2014/2015 academic year Curriculum 2013 is applied to the class I, II, IV, IV, VII, VIII, IX and X in all schools in Indonesia. This study conducted in Sumenep district Madura Island as supported study to monitoring and evaluation of Curriculum in 2013 on assessment system in East Java province. The research method used is descriptive qualitative by using observation, interviews and questionnaires techniques. The results showed optimism and expectations from respondents consist of teachers, headmasters and students in curriculum 2013’s assessment system. The findings are expected to support decision-making by stakeholders and improve the implementation of Curriculum 2013.